Group of Chippewa Indians. / Wm. Caswell & Co., Photographers, Duluth, Minn - Caswell, William, -1910 photographer. (William L. Clements Library, 1870)
Studio group portrait of six unidentified Ojibwa Indian men posing before illustrated backdrop wearing mixtures of western and traditional clothing including blankets, otter fur hair wraps and hair feathers. One man holds butcher knife while another holds hatchet. Sleeping dog in foreground.; Printed on left-hand margin: Wm. Caswell & Co., Photographers, Duluth, Minn.; Printed on right-hand margin: Scenery on the Northern Pacific Rail Road.; Title derived from image caption.; Original negative or series number?: 78.; "Ojibwa Indians" variant names: Anishinaabe, Chippewa Indians, Ojibwe Indians.